Chloroform-Methanol Extraction Antimicrobial Potential of Rheum Ribes Originating from Elazig/Aricak Province - Ozdemır, Oguzhan; Gok, Mesut; Toy, Nurten; Tuzcu, Zeynep (My University, 2023)
Rheum ribes (R. ribes) has a variety of medicinal applications due to the presence of anthraquinone derivatives and other compounds. It was aimed to determine the potential antimicrobial effects on some gram-negative/positive pathogens, and lactic acid bacteria by agar well diffusion test following minimum inhibition concentrations (MIC) with liquid extract samples of R. ribes. Growth concentrations of R. ribes extract doses (14.17-0,89 mg/L) were applied to indicator microorganisms. MIC method used microbial density values compared to the control group. Result of the Agar well diffusion test, the best antibacterial effects were detected on L. monocytogenes and S. aureus and following B. subtilis (zone diameter of 18.72 and 18.32 mm, respectively). The R. Ribes extract showed a higher inhibitor effect than tetracycline antibiotic against L. monocytogenes. Similarly, S. aureus and E. faecalis., S. paratyphi A were more affected by R. Ribes extract than tetracycline antibiotic. The MIC test result, the highest inhibitory effects of R. ribes extract at a concentration of 0,89 mg/L for S. Paratyphi A strain, 3.54 mg/L for K. pneumonia, and 3.54 mg/L for E. coli RSSK 09036 were determined as 50.81%, 60.45%, and 60.40%, respectively. The highest inhibition effects of R. ribes at 14.17 mg/L (0.5 dilution concentration) concentration were determined at the rate of 80.12% for Bacillus clausii and 96.04% for B. subtilis. In the present study, it is thought that the differences between the antimicrobial effect and MIC tests seen in gram-positive, negative and probiotic bacteria may be related to the surface tension effect of the extract
Keywords: Rheum ribes; antimicrobial activity; minimum inhibitory concentration; probiotic bacteria